Epistemic Cartography: Evaluating Net-Map as a Frontline Tool for Navigating Informal Knowledge Networks - Luke Metelerkamp; Eva Schiffer (Environmental Association of Southern Africa, 2020)
Sustainability transitions are dependent on the development and diffusion of transformative skills and competencies. However, the prevailing notion that learning for sustainability transitions will be led by universities, technical colleges and other similar institutions is practically not feasible in much of the global south. Net-Map is a social network analysis tool that uses interviews and mapping to help people understand, visualise, discuss, and improve situations in which many different actors influence outcomes (Schiffer & Hauck, 2010). In response to the pressing need for new approaches to the development and diffusion of sustainability skills, this paper evaluates Net-Map's suitability as a methodological tool for educators, knowledge brokers and students seeking to enhance the navigability of the often complex and uncharted occupational pathways they encounter. To do this, the research applied Net-Map to an emerging sustainability niche within the food system in order to map the learning pathways of successful sustainability pioneers. We found that Net-Map was helpful in identifying diffuse informal knowledge networks and teaching resources. Being free, quick to learn and easy to use, Net-Map is a potentially low-cost method for circumventing traditionally costly approaches to curriculum development and accreditation - assisting community-based actors to make sense of the informal knowledge and competency networks that support emerging career fields. In emerging career fields such as organic farming, where pioneer knowledge is fragmented, poorly documented and often disregarded by mainstream-science, Net-Map could be useful in the preparatory phase of curriculum planning and design, providing training designers, course conveners and facilitators with contextually informed insights.